Analisis Perbandingan Kepemimpinan HIMA pada UNAND Kampus II Payakumbuh, UNP, UNRI, dan UIN SUSKA Riau - Desri, Suryatman; Putri, Anelsa; Irwan, Suryadi (Lembaga Yasin AlSys, 2023)
A leader is a positive and confident person who has a vision, mission and high ethical values, with the ability to convey ideas and is able to encourage and relate well with others. Leadership will be a critical success factor in an organization. This is because leadership is the center point for significant changes in the organization, leadership becomes a personality that has an impact and leadership is an art in creating organizational fit and stability. Leaders in an organization have an important role in directing and influencing their subordinates. Without someone who regulates and directs an organization, the organization will surely be able to achieve its goals in accordance with its vision and mission. Therefore, a leader figure is needed to be able to manage and organize the organization to achieve its goals. Each person's way of leading must be different, be it how to communicate with subordinates or how to workflow. This study aims to examine the comparison of HIMA leadership at Andalas University, Campus II Payakumbuh, Padang State University, Riau University and Sultan Syarif Kasim Riau State Islamic University. This type of research is quantitative research by distributing questionnaires to students who take part in the HIMA organization at the four universities above.